Development and Validation of a Model to Predict Regression of Large Size Hepatocellular Adenoma. (August 2019) - Klompenhouwer, Anne Julia; Alblas, Maaike; van Rosmalen, Belle Vivica; Haring, Martinus Petrus Daniel; Venema, Esmee; Doukas, Michail; Thomeer, Maarten Guillaume Josephus; Takkenberg, Robert Bart; Verheij, Joanne; de Meijer, Vincent Erwin; van Gulik, Thomas Matthijs; Lingsma, Hester Floor; et al.
Abstract : INTRODUCTION: Surgery is advocated in hepatocellular adenomas (HCA) >5 cm that do not regress to <5 cm after 6–12 months. The aim of this study was to develop a model for these patients, estimating the probability of HCA regression to <5 cm at 1 and 2 years follow-up. METHODS: Data were derived from a multicenter retrospective cohort of female patients diagnosed with HCA >5 cm at first follow-up. Potential predictors included age, body mass index, and HCA diameter at diagnosis (T0), HCA-subtype (hepatocyte nuclear factor 1α inactivated HCA, inflammatory-HCA, unclassified HCA) and "T0-T1 regression-over-time" (percentage of regression between T0 and first follow-up (T1) divided by weeks between T0 and T1). Cox proportional hazards regression was used to develop a multivariable model with time to regression of HCA < 5 cm as outcome. Probabilities at 1 and 2 years follow-up were calculated. RESULTS: In total, 180 female patients were included. Median HCA diameter at T0 was 82.0 mm and at T1 65.0 mm. Eighty-one patients (45%) reached the clinical endpoint of regression to <5 cm after a median of 34 months. No complications occurred during follow-up. In multivariable analysis, the strongest predictors for regression to <5 cm were HCA diameter at T0 (logtransformed, hazard ratio (HR) 0.05), T0-T1 regression-over-time (HR 2.15) and HCA subtype inflammatory-HCA (HR 2.93) and unclassified HCA (HR 2.40), compared to hepatocyte nuclear factor 1α inactivated HCA (reference). The model yielded an internally validated c-index of 0.79. DISCUSSION: In patients diagnosed with HCA > 5 cm that still exceed 5 cm at first follow-up, regression to <5 cm can be predicted at 1 and 2 years follow-up using this model. Although external validation in an independent population is required, this model may aid in decision-making and potentially avoid unnecessary surgery.